Transforming growth factor beta orchestrates PD-L1 enrichment in tumor-derived exosomes and mediates CD8 T-cell dysfunction regulating early phosphorylation of TCR signalome in breast cancer. (24th August 2020) - Chatterjee, Soumya; Chatterjee, Annesha; Jana, Samir; Dey, Subhasis; Roy, Himansu; Das, Mrinal Kanti; Alam, Jahirul; Adhikary, Anindya; Chowdhury, Abhisek; Biswas, Anupam; Manna, Debasis; Bhattacharyya, Arindam
Abstract: Tumor cells promote immune evasion through upregulation of programmed death-ligand 1 (PD-L1) that binds with programmed cell death protein 1 (PD1) on cytotoxic T cells and promote dysfunction. Though therapeutic efficacy of anti-PD1 antibody has remarkable effects on different type of cancers it is less effective in breast cancer (BC). Hence, more details understanding of PD-L1-mediated immune evasion is necessary. Here, we report BC cells secrete extracellular vesicles in form of exosomes carry PD-L1 and are highly immunosuppressive. Transforming growth factor beta (TGF-β) present in tumor microenvironment orchestrates BC cell secreted exosomal PD-L1 load. Circulating exosomal PD-L1 content is highly correlated with tumor TGF-β level. The later also found to be significantly associated with CD8+CD39+, CD8+PD1+ T-cell phenotype. Recombinant TGF-β1 dose dependently induces PD-L1 expression in Texos in vitro and blocking of TGF-β dimmed exosomal PD-L1 level. PD-L1 knocked down exosomes failed to suppress effector activity of activated CD8 T cells like tumor exosomes. While understanding its effect on T-cell receptor signaling, we found siPD-L1 exosomes failed to block phosphorylation of src family proteins, linker for activation of T cells and phosphoinositide phospholipase Cγ of CD8 T cells more than PD-L1 exosomes. In vivo inhibition of exosome release and TGF-β synergistically attenuates tumor burden by promoting Granzyme and interferon gamma release in tumor tissue depicting rejuvenation of exhausted T cells. Thus, we establish TGF-β as a promoter of exosomal PD-L1 and unveil a mechanism that tumor cells follow to promote CD8 T-cell dysfunction. Abstract : TGF-β induces Texo PD-L1 load. Clinical results show positive correlation between exosomal PD-L1, TGF-β and CD8 T-cell dysfunction. siPD-L1 Texo failed to induce CD8 T-cell dysfunction ex vivo . TGF-β, texo release inhibition reduced breast tumor burden, induced CD8 T-cell effector activity.